2020
DOI: 10.1530/vb-20-0003
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography for monitoring severity and treatment of diabetic foot infections

Abstract: Monitoring of diabetic foot infections is largely based on clinical assessment, which is limited by moderate reliability. We conducted a prospective study to explore monitoring of thermal asymmetry (difference between mean plantar temperature of the affected and unaffected foot) for the assessment of severity of diabetic foot infections. In patients with moderate or severe diabetic foot infections (International Working Group on the Diabetic Foot infection-grades 3 or 4) we measured thermal asymmetry with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…One of the most common limitations in the assessment of diabetic foot disorders is that the contralateral foot analysis is prevented by the existence of partial foot amputations or deformations. In these cases, there is not a straightforward method to perform a comparison if the same deformation is not present on both feet or simply because the severity of the amputation does not allow it [15]. Furthermore, despite the fact that these are common features exhibited by persons affected by diabetic foot disorders, these patients are usually excluded from the assessment studies [15,46].…”
Section: Partial Foot Amputations or Deformationsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most common limitations in the assessment of diabetic foot disorders is that the contralateral foot analysis is prevented by the existence of partial foot amputations or deformations. In these cases, there is not a straightforward method to perform a comparison if the same deformation is not present on both feet or simply because the severity of the amputation does not allow it [15]. Furthermore, despite the fact that these are common features exhibited by persons affected by diabetic foot disorders, these patients are usually excluded from the assessment studies [15,46].…”
Section: Partial Foot Amputations or Deformationsmentioning
confidence: 99%
“…In these cases, there is not a straightforward method to perform a comparison if the same deformation is not present on both feet or simply because the severity of the amputation does not allow it [15]. Furthermore, despite the fact that these are common features exhibited by persons affected by diabetic foot disorders, these patients are usually excluded from the assessment studies [15,46].…”
Section: Partial Foot Amputations or Deformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermography as a complementary diagnostic support has been applied in medicine since the mid-1990s to detect various inflammatory diseases, complex regional pain syndrome or even Raynaud's phenomenon [16,17]. This tool also seems to be suitable for diagnoses of infectious processes, e.g., in postoperative wounds after cesarean section, in the feet of diabetics, or in a central venous catheter in children [18][19][20]. In the oral and maxillofacial area, studies have shown its potential for the diagnosis of various diseases such as traumatic fractures, osteomyelitis [21], malignant neoplasms, cervical lymph node metastasis from oral cancer [15], quantification of postsurgical inflammation after removal of wisdom teeth [22] and retained teeth [23], or arthralgia of temporomandibular joints [24].…”
Section: Introductionmentioning
confidence: 99%